Evaluación y capacitación del sistema de Seguridad industrial de la planta de fundición en La corporación ecuatoriana de aluminio Cedal. - Moreno Medina, Víctor Hugo (2011)
This research was made on the current organization of the Casting Plant in the enterprise “Cedal”. At the enterprise level, the labor risks and accidents are a serious problem, because there have been several incidents and accidents that directly affect business economics and the physical integrity of workers. It is true that there is industrial security system but the problems have given are the lack of training for its using in which the decision was made to perform the respective evaluation to continue its proper operation because the incidents and accidents cause disability. The present research work aims to reduce the presence of hazards, incidents, accidents and dangers or turn them. For which, I made inspections and identification of risks, which highlight all the risks and dangers that arise and affect the interior of the Casting Plant. This research proposes to perform The Evaluation and Training of the Industrial Safety System in the Casting Plant of the enterprise, in order to reduce accidents by providing safety to the personnel working in the casting plant.